A Survey On Securing Internet Of Medical Things Using Blockchain - et. al., Mrs.A.Susi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: In this project, we provide a solution to protect and secure the patient records and data against various attacks using the technology of blockchain. We use the fully decentralized blockchain. Also, digital signatures are used for model updates. Therefore, we hold that adversaries are not able to fabricate digital signatures or take control of the majority of the network. Furthermore, an adversary cannot poison the data because it is stored off-chain rather on the public ledger. There are only pointers information encrypted with a hash function inside a public ledger. In problems of large-grid-level centralized transactions and dispatch centers with information asymmetry and high processing costs, the proposal of a completely decentralized transaction architecture and a weak centralized scheduling strategy based on block-chain is done. Firstly, the defined concepts of transaction decentralization and scheduling decentralization are given, and the reliability of distributed transaction communication is studied. Based on the communication credit consensus mechanism, built a blockchain transaction risk control model. Secondly, security checks are performed under the weakly centralized scheduling architecture based on the autonomous chain of substations, and temporary central nodes are set up to perform scheduling tasks. Finally, an optimal solution is obtained by dynamically updating the credibility by using an improved evolutionary algorithm to solve the above model.